Management of traumatic pneumothorax in isolated blunt chest trauma - Sarıçam, Murat; Özkan, Berker; Türk, Yaşar (The European Research Journal, 2019)
Objectives: Pneumothorax is an important complication of blunt chest trauma. The aim of this study was to report our experience in treatment strategy and outcomes of traumatic pneumothorax. Methods: A total of 78 patients who developed pneumothorax due to isolated blunt chest trauma were evaluated in terms of age, gender, size of pneumothorax, treatment methods, complications and length of hospital stay. The size of pneumothorax was calculated with computer-aided volumetry. Results: Tube thoracostomy was performed for 48 patients while observation was undertaken for 30 cases. Chest tubes were inserted in 6 patients after 24 hours following the traumatic event. A total of 8 patients who developed prolonged air leakage and hemothorax as complications underwent video-assisted thoracoscopic surgery. None of the patients developed any mortality or morbidity. Conclusions: Traumatic pneumothorax demands prompt diagnosis and treatment. Monitoring all patients even with small sizes of traumatic pneumothorax for at least 24 hours onset of their initial assessment and applying chest tubes for cases who have pneumothorax larger than 50% at first examination should be an appropriate modality for treatment. Moreover, the minimally invasive approach of video-assisted thoracoscopic surgery benefits to overcome the complications of thoracic trauma.